Associations between NIHSS sub-item scores and prognosis and intracranial hemorrhage after endovascular therapy for acute anterior circulation ischemic stroke - Qi, Shuang; Shi, Mingchao; Li, Chao; Song, Kangjia; Zhou, Jie; Yue, Feixue; Zhang, Wenbin; Wang, Shouchun (Frontiers in Neurology, 2024)
Purpose The relationship between sub-item scores on the National Institutes of Health Stroke Scale (NIHSS) scores and prognosis and intracranial hemorrhage in patients with acute ischemic stroke undergoing endovascular treatment (EVT) has been insufficiently studied. The aim of this study was to investigate the correlation between NIHSS sub-item scores, prognosis, and intracranial hemorrhage. Methods This study included patients with acute anterior circulation ischemic stroke undergoing EVT between February 2019 and April 2022. The outcomes included functional independence, defined as a modified Rankin Scale (mRS) score ≤ 2 at 3 months after EVT, intracranial hemorrhage within 24 h after EVT, and mortality within 3 months. A multivariate regression analysis was performed, including NIHSS sub-item scores and other adjusted variables. Results A total of 568 patients were enrolled. Of the 568 patients, 239 (45%) achieved functional independence at 3 months after EVT. The median age in this group was 63 years (IQR 52–69) and 176 (73.6%) were male patients. Intracranial hemorrhage within 24 h after EVT occurred in 170 (30%) patients. The median age in this group was 65 years (IQR 56–71) and 105 (61.8%) were male patients. In a multivariate analysis adjusted for age, gender, and factors with a value of p of <0.05, the NIHSS limb movement sub-item score was strongly associated with prognosis at 3 months (OR 0.833, 95% CI 0.758–0.915) and intracranial hemorrhage within 24 h after EVT (OR 1.161, 95% CI 1.037–1.300). Conclusion Higher limb movement sub-item scores on the NIHSS were independently associated with a poorer prognosis at 3 months and a higher rate of intracranial hemorrhage within 24 h after EVT among patients with acute anterior circulation ischemic stroke.